2005
DOI: 10.3354/meps305101
|View full text |Cite
|
Sign up to set email alerts
|

Gonad fatty acids and trophic interactions of the echinoid Psammechinus miliaris

Abstract: Variation in gonadal somatic indices (GSI) and fatty acid signatures of 2 contrasting Scottish west coast populations of the echinoid Psammechinus miliaris were examined. P. miliaris was sampled from both the shallow subtidal and at the upper limit of its distribution in the intertidal. The intertidal population had a significantly higher GSI than the subtidal at both locations. Multivariate analysis (ANOSIM) of the fatty acid signature showed significant variation between the 2 depths as well as between sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 46 publications
3
36
0
1
Order By: Relevance
“…PUFAn-3: total polyunsaturated fatty acids of n-3 series. * P < 0.05 with respect to specimens collected at La Herradura reported for Psammechinus miliaris (Gmelin, 1178) by Hughes et al (2005Hughes et al ( , 2006. These authors found higher proportions of 14:0, 16:1n-7 and 18:4n-3 in females as well as higher levels of 18:0, 20:4n-6, 20:5n-3 and 22:6n-3 in males.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…PUFAn-3: total polyunsaturated fatty acids of n-3 series. * P < 0.05 with respect to specimens collected at La Herradura reported for Psammechinus miliaris (Gmelin, 1178) by Hughes et al (2005Hughes et al ( , 2006. These authors found higher proportions of 14:0, 16:1n-7 and 18:4n-3 in females as well as higher levels of 18:0, 20:4n-6, 20:5n-3 and 22:6n-3 in males.…”
Section: Discussionsupporting
confidence: 47%
“…The presence of 20 and 22 carbon NMI has been previously reported in the soft tissues of P. lividus (Serrazanetti et al 1995) as well as in other sea urchin species (Cook et al 2000;Liyana-Pathirana et al 2002b;Hughes et al 2005Hughes et al , 2006Takagi et al 1986). The exact physiological function of NMID has not been established; but because of their predominance in polar lipids, it has been suggested that they have functional and structural roles in membranes (KraVe et al 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Such a possibility is far from remote, as recent analyses have demonstrated true omnivory and even carnivory in chiton and fissurellid species from other coasts (Latyshev et al, 2004;Hughes et al, 2005;Grall et al, 2006). In addition, the existence of omnivory may have numerous implications for the understanding of food web structures and dynamics on rocky shores Sanhueza et al, 2008), and should not be neglected in experimental studies of community organization and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…FA tracers are also used to determine the fate of primary production, especially in habitats where the dominant primary producer is not directly consumed by the dominant herbivores (Meziane & Tsuchiya 2000, Kharlamenko et al 2001. Other field studies have employed FA analysis to address ecological questions about how animal diets vary with habitat, season, and anthropogenic effects (Takagi et al 1980, Hughes et al 2005, Fernandez-Jover et al 2007). …”
Section: Fa Analysis Of Benthic Food Websmentioning
confidence: 99%